Organization theory in humanitarian operations: a review and suggested research agenda - Chandra Prakash; Maria Besiou; Parikshit Charan; Sumeet Gupta (Journal of Humanitarian Logistics and Supply Chain Management)
Purpose – The purpose of this paper is to review the current application of organization theory (OT) in the humanitarian supply chain (HSC) and identify the future OT-based research opportunities that can advance knowledge of humanitarian operations. Design/methodology/approach – The study uses a systematic literature review methodology to identify the current status and future direction of the OT-based study in HSC literature. The applied theories are those that have been mentioned in at least two research articles in the HSC literature. The proposed theories are either adopted from the top four referred organizational theories in the supply chain literature or those that can explain the issue of information asymmetry in HSC. Findings – The study identifies and describes eight organizational theories and their possible future research questions in HSC. Among these, the first four theories (i.e. resource-based theory, resource dependence theory, social exchange theory and contingency theory) have already been initially applied in the humanitarian field, while the remaining theories (i.e. institutional theory, stakeholder theory, transactional cost theory and information theory) have potential for future application. Research limitations/implications – The reviewed literature is limited to peer-reviewed journals listed in Thomson Reuters’ journal citation reports. Practical implications – This study may help future researchers better understand and solve, using organizational theory, the behavioral challenges faced by humanitarian operations. Originality/value – The study presents current applications of and future prospects for OT-based research in HSC, effectively providing the first review of OT applications in this area. The novel framework and new theories proposed herein may enable fresh directions for HSC research.